HMGB3 is a Potential Therapeutic Target by Affecting the Migration and Proliferation of Colorectal Cancer - Gong, Wenjing; Guo, Yang; Yuan, Hang; Hu, Xinye; Chai, Rui; Zheng, Boan; Wan, Ziang; Tu, Shiliang (Frontiers in Cell and Developmental Biology, 2022)
Colorectal cancer is one of the common malignant tumors in the digestive system [1], with high incidence and mortality rate. Therefore, there is an urgent need to identify and develop new molecular targets for colorectal cancer treatment. Previous studies have pointed out the important role of HMGB3 in tumors, and how it works in colorectal cancer needs to be studied in depth. In this study, we found that HMGB3 was highly expressed in COAD in the cBioPortal and GEPIA2 databases. Kaplan-Meier analysis showed that compared with patients with lower HMGB3 levels, patients with higher HMGB3 levels patients with higher levels had poorer OS (P=0.001). We also found a correlation between HMGB3 expression and immune infiltration of CRC. To investigate the mechanism of HMGB3 knockdown-mediated colorectal cancer inhibition, we detected a downregulation of N-cadherin, Vimentin and β-catenin proteins after knockdown of HMGB3.Taken together, HMGB3 can be an effective target for CRC treatment in the future, and we have reason to believe that HMGB3 will be of greater value in more tumors in the near future.